Efficient removal of mercury and chromium from wastewater via biochar fabricated with steel slag: Performance and mechanisms - Wang, Huabin; Duan, Ran; Zhou, Xinquan; Wang, Jia; Liu, Ying; Xu, Rui; Liao, Zhuwei (Frontiers in Bioengineering and Biotechnology, 2022)
Biochar derived from biomass is regarded as a promising adsorbent for wastewater treatment, but the high cost of modification is still a challenge for its large-scale practical applications. In this study, we employed steel slag as a low-cost fabricant and synthesized the hydrothermally carbonized steel slag (HCSS), as a stable environmentally functional material for heavy metals removal. Typically, positively and negatively charged heavy metal contaminants of Hg2+ and Cr2O72-, were employed to testify the performance of HCSS as the adsorbent, and good capacities (283.24 mg/g for Hg(II) and 323.16 mg/g for Cr(VI)) were found. The feasibility of HCSS on real wastewater purification was also evaluated, as the removal efficiency was 94.11% and 88.65% for Hg(II) and Cr(VI), respectively. Mechanism studies revealed that the modification of steel slag on bio-adsorbents offered copious active sites for pollutants. As expected, oxygen-containing functional groups in HCSS acted as a main contributor to adsorption capacity. Moreover, some reactive iron species (i.e., Fe2+) played an essential role for chemical reduction of Cr(VI). The adsorptive reactions were pH-dependent, owing to other more mechanisms, such as co-precipitation, ion-exchange, and electrostatic attraction. This promising recycling approach of biomass waste and the design of agro-industrial byproducts can be highly suggestive to the issues of resource recovery in the application of solid waste-derived environmentally functional materials for the heavy metals remediation.